Reverse Saturable Absorption Induced by Phonon‐Assisted Anti‐Stokes Processes - Tian, Xiangling; Wei, Rongfei; Guo, Qianyi; Zhao, Yu‐Jun; Qiu, Jianrong (Advanced materials (Weinheim), 2018)
In materials showing reverse saturable absorption (RSA), optical transmittance decreases at intense laser irradiation. One approach to application of these materials is to protect the sensors or human eyes from laser damage. To date, research has mainly concentrated on thin films and suspensions of graphite and its nanostructure (including nanotubes, graphene, and graphene oxides), which are mainly used as an optical limiter for nanosecond laser pulses. Moreover, thin individual pieces of semiconductor usually exhibit increased transmittance due to saturable absorption when the laser energy (Elaser) is higher than the band gap (EB). Here, it is shown that indirect gap semiconductor WSe2 exhibits high RSA on exposure to a femtosecond laser under Elaser > EB near band gap excitation, which is attributed to the longitudinal optical phonon‐assisted anti‐Stokes transition by the annihilation of phonons and the absorption of photons. An optical limiting threshold (≈21.6 mJ cm−2) lower than those reported for other optical‐limiting materials currently for femtosecond laser at 800 nm is observed. Reverse saturable absorption induced by photon‐assisted anti‐Stokes processes in indirect semiconductor WSe2 when the irradiation energy is higher than the bandgap, is achieved via the annihilation of phonons and the absorption of photons. An optical limiting threshold of ≈21.6 mJ cm−2 makes the indirect semiconductor WSe2 promising for femtosecond optical limiting applications.